Job Embeddedness as A Moderator of The Influence of Organizational Justice on Turnover Intentions: Evidence from PT PupukSriwidjaja Palembang - , YOSEPHINE STELLA REMIDIA VIRANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Turnover Intention has become a serious problem for any organizations. An organization may have the most advanced processes or innovative technology, but success will not happen without the right people to make it all work and losing these people will surely create a big loss for any organizations. Employees with a great skill and potentials are the organizational best asset. Since the demand of professionals is huge, employees with skills are the ones who have the biggest chance to leave the organizations they currently working at for other organizations. It is very crucial for an organization to keep such a great potential employee. The symptoms of turnover intention can be seen from the way of employees delivering the service, their service recovery effort, and their morale in doing the job. These symptoms are driven by some related factors that catch the employees interest and basic needs such as job design, working environment, human resources practices, perceived justice in organization, etc. Organizational justice dimensions as a perceived fairness about the organization are used in this study as a proxy in explaining turnover intentions. It is important to understand the degree of fairness in outcomes, process conducted in decision-making, and the treatment received by an employee to manage turnover intention. Organizational justice as the employeesâ perception of fairness in organization can be the most effective way in understanding the workplace attitudes and behavior because organizational justice is likely to be found as a strong predictor of several important outcomes, especially turnover intention. A strong connection towards the organization and the job is expected to moderates the relationship between these justice dimensions and turnover intentions. Even so, there were only a few of empirical study which investigated about job embeddedness as a moderator variable of the influence of organizational justice on turnover intentions. Therefore, this research investigates job embeddedness as a moderator variable of the influence of organizational justice on turnover intentions in PT PupukSriwidajaja Palembang.The purpose of this research is to understand job embeddedness as a moderator variable of the influence of organizational justice on turnover intentions. This research was conducted to 300 employees of PT PupukSriwidjaja through offline questionnaires and analyzed by multiple regression analysis, but only 292 feedbacks were qualified to be analyzed. The result was all of these justice dimensions were negatively influenced turnover intentions and even if job embeddedness was expected to strengthen this relationship, this study did not provide any empirical support for job embeddedness as a moderating variable in the negative effect of procedural justice on turnover intentions.